2002
DOI: 10.1016/s0196-9781(01)00611-8
|View full text |Cite
|
Sign up to set email alerts
|

Central and peripheral regulation of gastric acid secretion by peptide YY

Abstract: Peptide YY (PYY) released postprandially from the ileum and colon displays a potent inhibition of cephalic and gastric phases of gastric acid secretion through both central and peripheral mechanisms. To modulate vagal regulation of gastric functions, circulating PYY enters the brain through the area postrema and the nucleus of the solitary tract, where it exerts a stimulatory action through PYY-preferring Y1-like receptors, and an inhibitory action through Y2 receptors. In the gastric mucosa, PYY binds to Y1 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 97 publications
(160 reference statements)
0
31
0
Order By: Relevance
“…The portal plasma levels of two neuropeptides, neuropeptide Y (NPY) and peptide YY (PYY), were also evaluated to assess the physiological consequences of the synbiotic treatment on the GI tract. Circulatory NPY and PYY display a profound inhibitory effect on gastric emptying and acid secretion, gut motility, and exocrine pancreatic secretion (52). The probiotic strains used in this study, i.e., Lactobacillus delbrueckii subsp.…”
mentioning
confidence: 99%
“…The portal plasma levels of two neuropeptides, neuropeptide Y (NPY) and peptide YY (PYY), were also evaluated to assess the physiological consequences of the synbiotic treatment on the GI tract. Circulatory NPY and PYY display a profound inhibitory effect on gastric emptying and acid secretion, gut motility, and exocrine pancreatic secretion (52). The probiotic strains used in this study, i.e., Lactobacillus delbrueckii subsp.…”
mentioning
confidence: 99%
“…It is of note that the Y 2 preferential agonist PYY-(3-36) infused intravenously at 75 pmol ⅐ kg Ϫ1 ⅐ h Ϫ1 shows a tendency to increase ethanol-induced gastric lesions. Previous studies indicate that Y 1 /PYY-preferring and Y 2 receptors can exert opposite effects on gastric function (8,40).…”
Section: Discussionmentioning
confidence: 98%
“…We previously reported that intravenous PYY-induced inhibition of gastric acid secretion was prevented by intracisternal injection of PYY antibody, providing evidence for a central action of peripheral PYY (42). In addition, microinjection of PYY or NPY into the DVC at low doses inhibits vagally stimulated gastric contractions, whereas higher doses induce a vagal-dependent stimulation of gastric acid and hepatic bile secretion as well as gastric motor function in urethane-anesthetized rats (8,40,(43)(44)(45). Our recent work also revealed that PYY injected intracisternally confers gastric protection against intragastric ethanol-induced gastric mucosal injury through vagal cholinergic-dependent pathways recruiting peripheral CGRP and nitric oxide (NO) mechanisms (20,41).…”
mentioning
confidence: 98%
“…Both peptides are released into the circulation in response to meal ingestion, with special reference to fats, and are widely considered as potential enterogastrones. Indeed, at physiologic doses, PYY and enteroglucagon may inhibit gastric acid secretion induced by pentagastrin, meal, and vagal stimulation (Adrian et al, 1985;Anini et al, 1999;Guo et al, 1987b;Sheikh, 1991;Walsh, 1994;Wettergren et al, 1994;Yang, 2002;Zeng et al, 1997). Although PYY and enteroglucagon colocalize in the same endocrine cell type and are usually released simultaneously, under certain conditions, only one peptide may be selectively released (Anini et al, 1999;Brubaker, 1991;Plaisancié et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…PYY may modulate gastric acid secretion induced by vagal stimulation, through Y 2 receptors located in the area postrema and in the dorsal vagal complex (Lloyd et al, 1996;Yang, 2002). Moreover, PYY does not interact directly with the parietal cells but may inhibit gastric acid secretion by Y 1 receptor activation on enterochromaffin-like cells, with the consequent blockage of histamine release (Zeng et al, 1997).…”
Section: Laforenza Et Almentioning
confidence: 99%